The shaping of the English landscape: An atlas of archaeology from the Bronze Age to Domesday Book - Green, C; Creswell, M (Archaeopress Publishing Ltd, 2021)
The Shaping of the English Landscape is an atlas of English archaeology covering the period from the middle Bronze Age (c. 1500 BC) to Domesday Book (AD 1086), encompassing the Bronze and Iron Ages, the Roman period, and the early medieval (Anglo-Saxon) age. It was produced as part of the English Landscape and Identities (EngLaId) project at the University of Oxford, which took place from 2011 to 2016, funded by the European Research Council.